A MODERN VIEW ON THE RELEVANCE OF THE PROBLEM OF NON-SPECIFIC ULCERATING COLITIS - Gulchehra Mardonalievna Akhmedova,; Umida Azizovna Asatullayeva,; Mirzaakhmedova Samira Lenorovna, (World Scientific Research Journal, 2025)
Ulcerative colitis (UC) is one of the most serious and unresolved problems in gastroenterology. UC is a common chronic disease of the colon, characterized by ulcerative and structural changes in the colon mucosa. Globally, it has an incidence of 50–230 cases per 110,000 people [1].  The disease can worsen at absolutely any age, but men and women aged 18-45 are especially susceptible. Colitis is twice as rare in smokers as in non-smokers. Many factors influence the development of this disease, the most common of which are: Infectious, immunological, genetic, and, of course, environmental factors. The disease is characterized by a long, persistent course, a tendency toward seasonal exacerbations and severe complications, a high rate of disability, and primarily affects young and middle-aged individuals of working age. In recent years, increasing importance has been attached to the state of the immune system in the pathogenesis of UC, which largely determines the outcome of the disease [1,2]. UC was first described in medical literature many centuries ago. The first description of the morphological picture of UC belongs to the Viennese pathologist Karl Rokitansky, which he presented in 1842 in a report “On catarrhal inflammation of the intestine.” Having performed several thousand autopsies on patients who died from infectious colitis, he described "ulcer-like colitis." Circular No. 4 in 1865 already contained a detailed description of the histological picture of UC, based on the study of over 200 autopsies. The disease has been described in follicles and glandular structures of the intestinal epithelium.